Etnosains Gerabah Banyuning Dalam Preservasi Ritus Dan Warisan Budaya Keagamaan Hindu - I Kadek Edi Palguna; I Kadek Abdhi Yasa; Made Reland Udayana Tangkas; I Gusti Ayu Desy Wahyuni; Kadek Anggie Noviari Dewi (Jurnal Penelitian Agama Hindu, 2026)
Banyuning ritual pottery, an intangible cultural heritage of the Balinese Hindu community, faces an existential threat due to the erosion of traditional knowledge (ethnoscience), a drastic decline in the number of artisans, and weak intergenerational transmission. This study aims to document and analyze the ethnoscience system in the production of Banyuning ritual pottery and to develop a participatory preservation model. The method employed is qualitative with an ethnographic approach, underpinned by an ethnoscience perspective. Data were collected through participant observation, in-depth interviews, and artifact analysis, followed by interactive and domain analysis. The findings reveal that the ethnoscience of Banyuning pottery is a holistic knowledge system integrated with Balinese Hindu cosmology (Tri Hita Karana and Panca Maha Bhuta), which implements knowledge transmission strategies and community-based preservation models. It is concluded that the preservation of Banyuning pottery requires a holistic approach integrating spiritual, social, economic, and ecological dimensions, through a synergy between traditional knowledge and modern strategies to ensure the sustainability of this cultural heritage in the contemporary era.